Relatives' experiences of brief admission in borderline personality disorder and self‐harming behaviour - Sally Hultsjö; Hanna Rosenlund; Lisa Wadsten; Rikard Wärdig (Wiley, 2023)
Abstract Aim The aim of this study is to describe experiences of brief admission (BA) of people with borderline personality disorder and self‐harming behaviour, from the perspective of their relatives. Design A descriptive qualitative design was chosen. Methods Twelve relatives of people with borderline personality disorder and self‐harming behaviour who had access to BA were interviewed. Data were analysed with qualitative conventional content analysis. Results One overarching category: Hope for the future and three categories occurred: Breathing space, Personal responsibility and Structure. BA created hope for the future and the relatives appreciated that BA is a freer and easily accessible form of care that enables help at an early stage, compared with usual care. When BA functions, the structure and pre‐determined days of care give relatives a breathing space, and the uncertainty diminishes for the children, as the parent can still be present during inpatient care. The lack of places was described as a disadvantage of BA.